Comparación de dos métódos de preparación de tejido para estudiar la anatomía interna del delfácido Tagosodes orizicolus con microscopia de luz y electrónica - Macaya Lizano, Ana Victoria (1997)
Two methods of embedding, sectioning and staining were developed to study the intemal anatomy of the delphacid planthopper Tagosodes orizicolus, one of the most important plagues of rice in Latín America and the only vector of the hoja blanca tenuiVirus (RHBV), using both light and electron rnicroscopy. The paraffinehematoxiline- eosine Y Iliethod allows tite color identification of tissues, for example purple for fat tissue, pink for muscles, yellow- brown for exocutícle, while the resin-toluidíne-blue method preserves hetter the ultrastructure but do not permit colór identification. The informatíon obtained by these procedures is complementary and the material can also be used for in situ studies by irnmunomicroscopy, to assess the changes in cell ultrastructure and the localizatíon and replication of the RHBV during its infection cycle in the insect vector.